2021
DOI: 10.1155/2021/2923441
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Serves as a Biomarker for Adverse Prognosis of ST-Segment Elevation Myocardial Infarction

Abstract: Objective. This study is aimed at exploring the underlying molecular mechanisms of ST-segment elevation myocardial infarction (STEMI) and provides potential clinical prognostic biomarkers for STEMI. Methods. The GSE60993 dataset was downloaded from the GEO database, and the differentially expressed genes (DEGs) between STEMI and control groups were screened. Enrichment analysis of the DEGs was subsequently performed using the DAVID database. A protein–protein interaction network was constructed, and hub genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Particularly, this miRNA was higher in NSTEMI than UA patients; moreover, a significant upregulation is reported in the STEMI group compared to the NSTEMI group. Xiao et al [ 64 ] concluded that miR-146a could be used as a new biomarker for adverse prognosis of STEMI; in particular, it may exert its function and its pathogenesis by targeting S100A12, a protein that is involved in the inflammatory response. J. Li et al [ 72 ] analyzed the predictive value of serum miR-203 for acute STEMI, concluding that this miRNA represents a potential new biomarker in the early prediction of STEMI.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, this miRNA was higher in NSTEMI than UA patients; moreover, a significant upregulation is reported in the STEMI group compared to the NSTEMI group. Xiao et al [ 64 ] concluded that miR-146a could be used as a new biomarker for adverse prognosis of STEMI; in particular, it may exert its function and its pathogenesis by targeting S100A12, a protein that is involved in the inflammatory response. J. Li et al [ 72 ] analyzed the predictive value of serum miR-203 for acute STEMI, concluding that this miRNA represents a potential new biomarker in the early prediction of STEMI.…”
Section: Resultsmentioning
confidence: 99%
“…Present study found that the incidence of MACE in the high-expression group was signi cantly higher than that in the low-expression group, high miR-146a expression level had a poor clinical prognosis than low miR-146a expression level in UA patients, indicating that miR-146a appears to be a reliable biomarker that could evaluate the severity of coronary artery stenosis and predict the prognosis among patients with UA. Xiao et al found that STEMI patients with high expression level of miR-146a had a higher risk of MACE than those with low expression level of miR-146a over 3-year follow-up period [29] . Scărlătescu AI et al found a relationship between the high level of miR-146a-5p and MACE in their research and proved that the expression level of miR-146a-5p is a predictor of MACE during one-year follow-up in STEMI patients [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Supporting these data, higher miR-146a-5p levels were encountered in patients with ACS compared with unstable angina [ 75 , 76 ]. Moreover, Xiao et al found that miR-146a might serve as a marker for MACE in STEMI patients [ 77 ].…”
Section: Discussionmentioning
confidence: 99%